LRIG2 promotes glioblastoma progression by modulating innate antitumor immunity through macrophage infiltration and polarization. Issue 9 (12th September 2022) - Hu, Jinyang; Dong, Feng; He, You; Xia, Xianyou; Cheng, Fangling; Chen, Sui; Hou, Xiaoshuang; Zhang, Po; Liu, Guohao; Li, Ying; Gao, Qian; Dong, Minhai; et al.
Abstract : Background: Glioblastoma (GBM) is the most common malignant brain tumor with poor clinical outcomes. Immunotherapy has recently been an attractive and promising treatment of extracranial malignancies, however, most of clinical trials for GBM immunotherapy failed due to predominant accumulation of tumor-associated microglia/macrophages (TAMs). Results: High level of LRIG2/soluble LRIG2 (sLRIG2) expression activates immune-related signaling pathways, which are associated with poor prognosis in GBM patients. LRIG2/sLRIGs promotes CD47 expression and facilitates TAM recruitment. Blockade of CD47–SIRPα interactions and inhibition of sLRIG2 secretion synergistically suppress GBM progression in an orthotropic murine GBM model. Conclusions: GBM cells with high level LRIG2 escape the phagocytosis by TAM via the CD47-SIRPα axis, highlighting a necessity for an early stage of clinical trial targeting LRIG2 and CD47-SIRPα as a novel treatment for patients with GBM.